Non-suicidal self-injury: A bibliometrics study and visualization analysis from 2002 to 2022 - Dong, Xiangli; Zou, Yuchen; Zou, Qing; Zhao, Na; Li, Shilin; Liu, Guanxiu; Hu, Maorong; Sun, Weiming (Frontiers in Psychiatry, 2023)
Objective: To overview the research actuality and offer the hotspots and cutting-edge issues in the field of Non-suicidal Self-injury(NSSI) by using bibliometric analysis. Methods: Publications related to NSSI from inception(2006) to 2022 were extracted from the Web of Science Core Collection(WoSCC) database. CiteSpace(5.8.R3) was used to visually analyzed institutions, countries, journals, authors, references and keywords in research on NSSI. Results: A total of 974 studies about NSSI were analyzed via CiteSpace. The number of publications gradually increased totally and will continue to increase in 2022. The USA and Katholieke University Leuven are the most productive country and institutions. In the case of journals and co-cited journals, archives of suicide research are the most productive journal, and SUICIDE LIFE-THREAT is ranked highest among co-cited journals. Furthermore, Laurence Claes has published the most publications, and NOCK MK is the most cited author. An article published by Sarah V Swannell et al. shows the highest citation counts. After analysis, the most common keywords are harm, behavior, and prevalence. The meta-analysis, ecological momentary assessment, and people are frontier areas of NSSI research. Conclusions: This study analyzed the research of NSSI from multiple perspectives, and provides valuable information for researchers to capture the current status, hot spots and frontier trends of NSSI.